The responses of contemporary South African children to threshold experiences in Grimm fairy tales and African folk tales - Wolpert, Stacey (My University, 2008)
This study investigates the responses of contemporary South African, Grade one children to threshold experiences in Grimm fairy tales and African Zulu folk tales. Thresholds involve an exciting or challenging experience, or a transformation in stories. Three stories from each genre were read over six sessions, to ten diverse black and white children, from one school. The children’s enjoyment was assessed, with focus on their backgrounds and previous knowledge, to help find beneficial reading for them. Results suggested that while gender of characters and story origins did not seem important, story length, humour, entertainment and educational ability, as well as personal involvement, were useful. The study supported the notion that stories are generally universal and could help bridge our cultural divide. Reader-Response theory was used and its principles helped to structure questions for the interviews, and to analyse data. Hopefully, the findings will help to select appropriate texts for all children beginning school in present-day South Africa.
Keywords: fairy tales; folk tales; children's literature; South African children; Grimm; African stories; African folk tales